2010
DOI: 10.1002/cm.20429
|View full text |Cite
|
Sign up to set email alerts
|

A central role for the WH2 domain of Srv2/CAP in recharging actin monomers to drive actin turnover in vitro and in vivo

Abstract: Cellular processes propelled by actin polymerization require rapid disassembly of filaments, and then efficient recycling of ADF/cofilin-bound ADP-actin monomers back to an assemblycompetent ATP-bound state. How monomer recharging is regulated in vivo is still not well understood, but recent work suggests the involvement of the ubiquitous actin-monomer binding protein Srv2/CAP. To better understand Srv2/CAP mechanism, we explored the contribution of its WH2 domain, the function of which has remained highly elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(117 citation statements)
references
References 43 publications
(73 reference statements)
7
108
1
1
Order By: Relevance
“…Further, C-CAP1-98 (which mutates a key actin-binding surface on the WH2 domain) almost completely abolished the activity. These results demonstrate that the WH2 domain of CAP1 is critical for actin monomer recycling specifically in the presence of cofilin, similar to what has been observed for yeast Srv2 (23). Thus, the mechanisms used by yeast and mammalian CAP homologs for catalyzing actin monomer recycling appear to be highly conserved.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Further, C-CAP1-98 (which mutates a key actin-binding surface on the WH2 domain) almost completely abolished the activity. These results demonstrate that the WH2 domain of CAP1 is critical for actin monomer recycling specifically in the presence of cofilin, similar to what has been observed for yeast Srv2 (23). Thus, the mechanisms used by yeast and mammalian CAP homologs for catalyzing actin monomer recycling appear to be highly conserved.…”
Section: Discussionsupporting
confidence: 80%
“…However, earlier studies on yeast Srv2 showed that mutating the central pair of Lys residues in its LKKV motif had little effect on function either in vitro or in vivo (18,23). Instead, mutating both of the flanking hydrophobic residues (Leu and Val) was required to disrupt WH2 function in vitro and in vivo (23).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations